'HOPING AGAINST HOPE’: THE PRDS MOVEMENT AND THECREATION OF ITS DISCURSIVE TERRAIN; AN EXPLORATION OF A'LOWER CASTE' MOVEMENT IN KERALA AND ITS SOCIO-CULTURAL IMPACT (1890-1950C.E) - Malavika Binny
The paper seeks to explore the socio-religious movement for upward mobility by 'dalit 2 'Christians in Kerala in South India called the PRDS (Prathyaksha Raksha Daiva Sabha) movement in the twilight years of the nineteenth century and the early decades of the twentieth century emphasising on a phenomenological approach. The distinctive feature of the movement was that it not only emerged from among one of the most oppressed communities in India, but that the movement created its own teleological discourse borrowing from Biblical imagery but juxtaposing it unto the social and cultural landscape of Kerala. The paper intends to investigate the creation of a 'new' religio-cultural discourse by the movement in which the idea of hope played a seminal function. The theme of hope found a profound resonance in the movement and it was heavily loaded with multiple layers of social and semiotic meanings. Hope, for instance was understood as the hope of the emancipation of the 'slave-caste' from the hierarchical and discriminative caste system, but it was also hope in the form of redemption through the cleansing of sins and the hope for eternity which could be attained by stripping off the baggage of both the traditions of Christianity and Hinduism. The paper shall attempt to analyse the movement which was aimed at and achieved considerable social mobility by probing its rich discursive terrain which manifest itself in the form of books, songs and the invention of a new liturgy and a ritual world which sought to redefine the identity of the 'lower caste' Christians through a re-configuration of both 'time andbeing’ for both caste mobilisation and identity creation. Archival material from the Kerala State and the National Archives of India, oral interviews and hagiographies of Poikayyil Yohannan will alsobe used for the purposes of the study.